Laser Fenestration of Aortic Stent-Grafts Followed by Noncompliant vs Cutting Balloon Dilation: A Scanning Electron Microscopy Study. (June 2018) - Lin, Jing; Parikh, Niraj; Udgiri, Naval; Wang, Shaoxia; Miller, Daniel F.; Li, Chaojing; Panneton, Jean; Nutley, Mark; Zhang, Ze; Huang, Yunfan; Lu, Jun; Zhang, Jingyi; et al.
Purpose: To examine the effects of in situ laser fenestration and subsequent balloon dilation (noncompliant vs cutting) on the graft fabric of 4 aortic stent-graft models.Method: In an in vitro setup, the Zenith TX2, Talent, Endurant, and Anaconda aortic stent-grafts (all made of polyester graft material) were subjected to laser fenestration with a 2.3-mm-diameter probe at low and high energy in a physiologic saline solution followed by balloon dilation of the hole. For the first series of tests, 6-mm-diameter noncompliant balloons were used and replaced for the second series by 6-mm-diameter cutting balloons. Each procedure was performed 5 times (5 fenestrations per balloon type). The fenestrations were examined visually and with light and scanning electron microscopy.Results: Each fenestration demonstrated various degrees of fraying and/or tearing regardless of the device. The monofilament twill weave of the Talent endograft tore in the warp direction up to 7.09±0.46 mm at high energy compared with 2.41±0.26 mm for the Endurant multifilament device. The fenestrations of the 3 endografts with multifilament weave (Zenith, Anaconda, and Endurant) showed more fraying; fenestration areas in the multifilament Endurant were >10 mm 2 at low and high energy. The fenestrations were free of melted fibers, but minor blackening of the filaments was observed in all devices. Overall, the cutting balloons resulted in worse tearing and damage. Of note, the edges of the dilated laser-formed fenestrations of the Talent and the Endurant grafts demonstrated evidence of additional shredded yarns.Conclusion: In situ fenestration does not cause any melting of the polyester; however, the observed structural damage to the fabric construction must be carefully considered. Cutting balloons caused various levels of tearing compared to the noncompliant balloons and cannot be recommended for use in this application. Rather, noncompliant balloons should be employed, but only with endografts constructed from multifilament yarns. The use of in situ fenestration must be restricted to urgent and emergent cases until long-term durability can be determined.